Água virtual em diferentes formas de produção/comercialização de alimentos no município de Erechim (RS) - Lunardi, James (2013)
This research brings an approach of the quantifyingof virtual water built-in food in different forms of production and trading. This theme suggests new fronts of analysis in the researchof water resources,bringing the water footprint as well as a new tool for this purpose. Environmental education and sustainability enter this bulge showing the changes which presented a series of data highlighting this issue. The main objective of this research was to analyze the quantity of water that is attached to these products. These products are gotten from long distances and are marketed in Erechim and with the distance of transportation , the environment is impacted with a large water use. Otherside we tried to know about these products obtained with a lesser proximity of their trading, just to balance this calculation of the virtual water . This comparison brought information that the same product can be more sustainable, and less aggressive to the environment, to the point of just having in their method of production and trading a the differential form of production with minor uses of pesticides and marketing, being nearer the production , which it is consuming a heightened amount of virtual water. This water is virtual, however, is precisely calculated to give a warning to society that consumes a product that ends up detaching of sustainability. It is concluded that food produced in long distances consuming a large amount of virtual water and just because they are large quantities transported in long distances, they suffer amortization obtained through calculations. These amounts of virtual water embedded in major life cycle of the products surveyed and ownership of water resources in the forms of production generate major concerns.